Effects of laser offset and hybrid welding on microstructure and IMC in Fe–Al dissimilar welding - Casalino, Giuseppe; Leo, Paola; Mortello, Michelangelo; Perulli, Patrizia; Varone, Alessandra (MDPI, 2017)
Welding between Fe and Al alloys is difficult because of a significant difference in thermal properties and poor mutual solid-state solubility. This affects the weld microstructure and causes the formation of brittle intermetallic compounds (IMCs). The present study aims to explore the weld microstructure and those compounds over two different technologies: the laser offset welding and the hybrid laser-MIG (Metal inert gas) welding. The former consists of focusing the laser beam on the top surface of one of the two plates at a certain distance (offset) from the interfaces. Such a method minimizes the interaction between elevated temperature liquid phases. The latter combines the laser with a MIG/MAG arc, which helps in bridging the gap and stabilizing the weld pool. AISI 316 stainless steel and AA5754 aluminum alloy were welded together in butt configuration. The microstructure was characterized and the microhardness was measured. The energy dispersive spectroscopy/X-ray Diffraction (EDS/XRD) analysis revealed the composition of the intermetallic compounds. Laser offset welding significantly reduced the content of cracks and promoted a narrower intermetallic layer.
Keywords: Laser offset welding; Hybrid welding; Microstructure; Intermetallic layer